Use of a resin material as an adsorbent for noble metals in a liquid

CN122958646APending Publication Date: 2026-10-23DALIAN INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510506088.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-22
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

[0003]专利CN86103557A保护了一种一种能分离富集贵金属的树脂,采用离子交换的方法实现贵金属的分离,但是这种方法对铑、铱分离效果有限,选择性不足

Benefits of technology

[0038]该方法简单易行,效果显著,对贵金属吸附容量大、效率高、选择性好,不受其他金属影响,最为关键的是可以将吸附后溶液中的贵金属残留量控制在1ppb以下(有S配体辅助情况下),适用于工业废水、电子废弃物及矿石浸出液中贵金属的回收及医药、食品等的超纯净化。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122958646A_ABST
    Figure CN122958646A_ABST
Patent Text Reader

Abstract

The application belongs to the field of high polymer materials and environmental purification, and particularly relates to a method for efficiently and selectively adsorbing and separating noble metals such as Pt, Pd, Rh and Ir from complex organic and / or inorganic solutions by using a P / S(N)-containing porous organic polymer resin material with a large specific surface area, developed pores and good stability and application thereof. The P / S(N)-containing resin material has a large adsorption capacity for noble metals, high efficiency and good selectivity, is not affected by other metals, and most importantly, can control the residual amount of noble metals in the solution after adsorption to be below 10 ppb, and is suitable for the recovery of noble metals in industrial wastewater, electronic waste and ore leaching solution and the ultra-purification of medicines, foods and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of polymer materials and environmental purification, specifically relating to a resin material with high selective adsorption of precious metals and its application. Background Technology

[0002] Precious metals are widely used in chemical, light industry, aerospace, military, pharmaceutical, and environmental protection fields, and are known as the "vitamins of modern industry." However, precious metals are extremely scarce in the Earth's crust, making them a very limited resource relative to ever-increasing demand. There is an urgent need to develop new and efficient precious metal enrichment and separation technologies (Wang Shuai, Synthesis of Polyester-Based Sulfur Resin and its Adsorption and Separation Performance for Precious Metal Ions, Doctoral Dissertation, Central South University, 2008). Furthermore, in the pharmaceutical and food industries, precious metals are used as catalysts in product manufacturing, and the end products require extremely low precious metal content, necessitating the development of highly selective, low-residue adsorption materials.

[0003] Patent CN86103557A protects a resin capable of separating and enriching precious metals, using ion exchange to achieve the separation of precious metals. However, this method has limited effectiveness and selectivity in separating rhodium and iridium. Patent (CN109385525B) proposes a method for separating platinum and rhodium from alkaline cyanide solution using polystyrene-tributyl quaternary phosphine resin, but it is limited to use under alkaline conditions. Summary of the Invention

[0004] In order to easily achieve highly selective adsorption and separation of precious metals, the present invention aims to provide a resin material and its application that can improve the selective adsorption of precious metals.

[0005] The technical solution of this invention is as follows:

[0006] A resin material with high selectivity for adsorbing precious metals and its application, wherein the resin material uses one or more P ligands containing olefin groups as polymerizing monomers, and is crosslinked by olefin self-polymerization or copolymerization with S / N ligands containing olefin groups to form a resin material with large specific surface area, well-developed pores and good stability.

[0007] The specific surface area of ​​resin materials is 20-2000 m². 2 / g, preferably in the range of 100-1200m 2 / g; pore volume is 0.1-5.0cm³ 3 / g, preferably 0.5-2.0cm 3 / g; pore size distribution is 0.01-100.0nm, preferably 0.1-20.0nm.

[0008] The resin material is prepared by self-polymerization of P-ligands containing olefin groups or by self-polymerization or copolymerization with S-ligands containing olefin groups.

[0009] The olefin-containing P-ligand comprises one or more of monodentate and polydentate phosphine ligands, wherein the olefin group is preferably vinyl; it is selected from one or more of the following structures:

[0010]

[0011]

[0012]

[0013]

[0014]

[0015]

[0016] L1-L59 are monophosphine ligands, and B1-B18 are multidentate phosphine ligands.

[0017] The olefinic group in the S- and / or N-containing ligands containing an olefinic group is preferably vinyl, and the ligands containing an olefinic group S and / or N are selected from one or more of the following structures:

[0018]

[0019] The preparation process of resin materials is as follows:

[0020] After dissolving one or more phosphine ligands containing olefin groups, if a copolymerization scheme is adopted and S and / or N monomers containing olefin groups are added, the olefin groups are polymerized by bulk polymerization, emulsion polymerization or suspension polymerization, and a free radical initiator is used to initiate the polymerization reaction of the olefin groups to generate a polymer. This polymer can be used as an excellent resin material for selectively adsorbing noble metals.

[0021] The specific preparation steps of the resin material are as follows:

[0022] a) Under an inert atmosphere of 273-473 K, add one or more phosphine ligands containing olefin groups to the solvent. When adopting a copolymerization scheme, add a second ligand containing olefin groups containing S and / or N. Add a free radical initiator and stir the mixture for 0.1-50 hours to obtain a prepolymer solution. The preferred stirring time range is 1-10 hours.

[0023] b) The prepolymer mixture obtained in step a) is subjected to polymerization reaction (by bulk polymerization, suspension polymerization or emulsion polymerization) under an inert atmosphere of 273-473K for 1-100 hours to obtain a phosphine-containing organic polymer.

[0024] c) Remove the solvent from the phosphine ligand polymer containing S and / or N obtained in step b) to obtain an organic polymer with a hierarchical porous structure containing exposed P and S and / or N, i.e., the resin material that selectively adsorbs noble metals.

[0025] The organic solvent in step a) is one or more of the following: benzene, toluene, xylene, biphenyl, polychlorinated biphenyl, cyclohexane, n-octane, dodecane, methanol, ethanol, dichloromethane, chloroform, 1,4-dioxane, tetrahydrofuran, and methyltetrahydrofuran.

[0026] The free radical initiator mentioned in step a) is one or more of cyclohexanone peroxide, benzoyl peroxide, tert-butyl hydroperoxide, or azobisisobutyronitrile;

[0027] In step b), when suspension polymerization or emulsion polymerization is adopted, the suspension emulsifier is selected from one or more of polyvinyl alcohol, polyvinylpyrrolidone, p-octylphenol polyoxyethylene ether, N-dodecyl dimethylamine, sodium stearate and calcium dodecylbenzenesulfonate; the volume ratio of oil phase to water phase in suspension or emulsion polymerization is 10000:1-1:10000 (preferably 1000:1-1:1000);

[0028] In step a), before polymerization into an organic polymer, the concentration of the phosphine ligand containing an olefin group in the solvent ranges from 0.01 to 1000 g / L, preferably from 0.1 to 100 g / L, the molar ratio of the second component containing an olefin group (S and / or N) to the phosphine ligand is 0.0001:1 to 10000:1 (preferably 0.001:1 to 1000:1), and the molar ratio of the phosphine ligand containing an olefin group to the free radical initiator is 5000:1 to 10:1, preferably 1000:1 to 10:1.

[0029] The inert gas mentioned in steps a) and b) is selected from one or more of Ar, He, N2 and CO2.

[0030] Applications of the resin material obtained by the preparation method for highly selective adsorption of noble metals:

[0031] This method can be applied to the recovery of precious metals from industrial wastewater, electronic waste and ore leachate, as well as the ultrapurification of pharmaceuticals, food and other products. The adsorption operation can be carried out in fixed bed, moving bed or fluidized bed adsorption modes.

[0032] Because it is formed by cross-linking of olefin groups, the resin material has stable physicochemical properties under the condition of adsorbing noble metals, is resistant to acids and alkalis, and can be used for the selective separation of noble metals in complex organic and inorganic solutions, preferably inorganic solutions. The operating temperature range is -50-400℃, and the pH range is 1-13, preferably 1-6.

[0033] Due to the high concentration of P / S(N) adsorption sites in the resin material framework, it has a large adsorption capacity and high selectivity for precious metals. It can efficiently and selectively adsorb and separate precious metals such as Pt, Pd, Rh, and Ir in complex organic and / or inorganic solutions, unaffected by other metals, and can ultimately control the residual amount of precious metals in the solution after adsorption to below 10 ppb.

[0034] The reaction principle of this invention:

[0035] This invention utilizes free radical polymerization to adsorb high concentrations of phosphorus ligands (up to 2.95 mmol / g or higher). High-concentration phosphorus ligands exhibit strong coordination with noble metals, resulting in a large adsorption capacity and low metal residue. Simultaneously, the phosphorus in the framework has relatively weak coordination with non-noble metals such as Na+, Mg2+, Ca2+, Cu2+, and Ni2+, thus demonstrating good adsorption selectivity for noble metals.

[0036] This invention relates to a method and its application for the efficient and selective adsorption and separation of precious metals such as Pt, Pd, Rh, and Ir from complex organic and / or inorganic solutions using a P / S(N) porous organic polymer resin material with a large specific surface area, well-developed pores, and good stability. The P / S(N) resin material involved in this invention has a large adsorption capacity, high efficiency, and good selectivity for precious metals, and is not affected by other metals. Most importantly, it can control the residual amount of precious metals in the solution after adsorption to below 10 ppb. It is suitable for the recovery of precious metals from industrial wastewater, electronic waste, and ore leachate, as well as for the ultrapurification of pharmaceuticals, food, etc.

[0037] The beneficial effects of this invention are as follows:

[0038] This method is simple and easy to implement, with significant effects. It has a large adsorption capacity for precious metals, high efficiency, and good selectivity, and is not affected by other metals. Most importantly, it can control the residual amount of precious metals in the solution after adsorption to below 1 ppb (with the assistance of S ligand). It is suitable for the recovery of precious metals from industrial wastewater, electronic waste and ore leachate, as well as for the ultrapurification of pharmaceuticals, food and other products. Attached Figure Description

[0039] Figure 1 It is the molecular formula of the second component accelerator containing S and N.

[0040] Figure 2 The thermogravimetric analysis (TGA) of the resin material prepared in Example 1 under an N2 atmosphere shows that this type of resin material can maintain skeletal stability under an inert gas atmosphere at 425°C.

[0041] Figure 3 The N2 physical adsorption curve of the resin material prepared in Example 1 shows that this type of resin material has well-developed pores and a relatively large specific surface area. Detailed Implementation

[0042] The following embodiments provide a better illustration of the present invention, but do not limit the scope of protection of the present invention.

[0043] Example 1

[0044] The resin is prepared by: under a protective atmosphere of 285K and inert gas N2, 90.0 g of monomer... (The synthesis process can be found in the literature Chem. Commun. 2014, 50, 11844-11847) and 10.0 g of the second component. Dissolve the azobisisobutyronitrile (AIOBR) in 500.0 ml of methyltetrahydrofuran solvent. Add 2.0 g of AIOBR, a free radical initiator, to the above solution and stir for 1.0 h to obtain a prepolymer. Transfer the prepolymer to an autoclave and polymerize it at 383 K under an inert N2 atmosphere using a solvothermal polymerization method for 24 h. After the polymerization vessel cools to room temperature, remove the solvent under vacuum at 333 K to obtain the phosphine ligand organic polymer (its physical adsorption and thermogravimetric curves are shown in [reference needed]). Figure 2 and Figure 3 It can be used as a resin material for subsequent highly selective adsorption of precious metals, with a pore volume of 1.52 cm³. 3 / g, pore size distribution 0.1-20nm, specific surface area 1004m² 2 / g.

[0045] Example 2

[0046] In Example 2, in the resin preparation steps, besides weighing 80.0 grams of monomer... and 10.0g monomer (The synthesis process is described in patent ZL 201410805880.X) Replaces 90.0 g of monomer. Apart from the above, the rest of the synthesis process and conditions were the same as in Example 1, and the resulting material had a pore volume of 1.15 cm³. 3 / g, pore size distribution 0.1-20nm, specific surface area 990m² 2 / g.

[0047] Example 3

[0048] In Example 3, during the resin preparation step, in addition to weighing 10.0g of the second component... Replace 10.0g of the second component Except for the above, the rest of the synthesis process and conditions were the same as in Example 1. The Rh metal loading of the obtained catalyst was 0.25%, and the pore volume of the obtained material was 1.32 cm³. 3 / g, pore size distribution 0.1-20nm, specific surface area 1065m² 2 / g.

[0049] Example 4

[0050] In Example 4, during the resin preparation step, in addition to weighing 10.0g of the second component... Replace 10.0g of the second component Except for the synthesis process and conditions, the rest were the same as in Example 1. The resulting material had a pore volume of 1.55 cm³. 3 / g, pore size distribution 0.1-20nm, specific surface area 1006m² 2 / g.

[0051] Example 5

[0052] In Example 5, during the resin preparation step, in addition to weighing 10.0g of the second component... Replace 10.0g of the second component Except for the above, the rest of the synthesis process is the same as in Example 1. The resulting material has a pore volume of 1.39 cm³. 3 / g, pore size distribution 0.1-20nm, specific surface area 994m² 2 / g.

[0053] Example 6

[0054] In Example 6, during the resin preparation step, in addition to weighing 10.0g of the second component... Replace 10.0g of the second component Except for the synthesis process and conditions, the rest were the same as in Example 1. The pore volume of the obtained material was 1.31 cm³. 3 / g, pore size distribution 0.1-20nm, specific surface area 958m² 2 / g.

[0055] Example 7

[0056] In Example 7, the resin preparation step was performed without adding the second component. Except for the above, the rest of the synthesis process and conditions were the same as in Example 1. The resulting resin had a pore volume of 1.45 cm³. 3 / g, pore size distribution 0.1-20nm, specific surface area 1090m² 2 / g.

[0057] Example 8

[0058] In Example 8, the resin preparation steps were performed without adding the second component. Except for the above, the rest of the synthesis process and conditions were the same as in Example 2. The resulting resin had a pore volume of 1.21 cm³. 3 / g, pore size distribution 0.1-20nm, specific surface area 1023m² 2 / g.

[0059] Comparative Example 1

[0060] In Comparative Example 1, except for the use of an equal mass of the second component... Alternative Except for the above, the rest of the synthesis process and conditions were the same as in Example 1. The resulting resin had a pore volume of 1.14 cm³. 3 / g, pore size distribution 0.1-20nm, specific surface area 869m² 2 / g.

[0061] Comparative Example 2

[0062] In Comparative Example 2, except for the use of an equal mass of the second component... Alternative Except for the synthesis process and conditions, the rest were the same as in Example 1. The resulting resin had a pore volume of 1.30 cm³. 3 / g, pore size distribution 0.1-20nm, specific surface area 967m² 2 / g.

[0063] Comparative Example 3

[0064] In Comparative Example 3, except for not adding In addition to the ligand, the remaining synthesis process and conditions were the same as in Example 1, yielding... The self-polymerized resin had a pore volume of 0.32 cm³. 3 / g, pore size distribution 0.01-20nm, specific surface area 254m² 2 / g.

[0065] Comparative Example 4

[0066] In addition to using equal quality Alternative In addition to the ligand, the remaining synthesis process and conditions were the same as in Example 7, yielding... The self-polymerized resin had a pore volume of 1.01 cm³. 3 / g, pore size distribution 0.01-15nm, specific surface area 902m² 2 / g.

[0067] Comparative Example 5

[0068] In addition to using equal quality Alternative In addition to the ligand, the remaining synthesis process and conditions were the same as in Example 7, yielding... The self-polymerized resin had a pore volume of 0.95 cm³. 3 / g, pore size distribution 0.01-10nm, specific surface area 830m² 2 / g.

[0069] Comparative Example 6

[0070] In addition to using a second component of equal mass Alternative Except for the above, the rest of the synthesis process and conditions were the same as in Example 1. The resulting resin had a pore volume of 1.08 cm³. 3 / g, pore size distribution 0.1-20nm, specific surface area 854m² 2 / g.

[0071] Comparative Example 7

[0072] In addition to using a second component of equal mass Alternative Except for the synthesis process and conditions, the rest were the same as in Example 1. The resulting resin had a pore volume of 1.10 cm³. 3 / g, pore size distribution 0.1-20nm, specific surface area 888m² 2 / g.

[0073] Example 9

[0074] A mixed aqueous solution of Rh(III), Pd(III), Ir(III), Pt(III) and Na(I), Cu(II) metal ions with concentrations of 0.1 mol / L was prepared. 10 g of the resin material prepared in Examples 1-9 and Comparative Examples 1-7 was added to 100 ml of the mixed solution, respectively. The adsorption temperature was controlled at 25 °C, and the adsorption time was 2 hours. After adsorption, the concentration of metal ions in the mixed solution was detected by ICP-MS, and the results are listed in Table 1.

[0075] Table 1. Ion concentrations in the mixed solutions after resin adsorption in Examples 1-9 and Comparative Examples

[0076]

[0077] As shown in Table 1, under the same conditions, the phosphine ligand polymer resin in Example 7 can desorb Rh(III), Pd(III), Ir(III), and Pt(III) to below 10 ppb, but its desorption performance for non-noble metals such as Na(I) and Cu(II) is poor. Example 8 is a single-phosphine and bisphosphine copolymer resin, which has slightly better desorption performance for noble metals than Example 7. Examples 1-6 are S / N ligand-doped P ligand resins. With the assistance of S and / or N, the resin materials have better desorption performance than the P ligand-only resin in Example 7. They can desorb Rh(III), Pd(III), Ir(III), and Pt(III) to below 5 ppb. However, not all S / N ligands have a promoting effect. The non-preferred S / N ligands in Comparative Examples 1 and 2 not only did not promote the desorption of noble metals, but also had the opposite effect. The data from Comparative Example 3 shows that if the resin material backbone has no P functional sites and only S functional sites, the desorption ability for noble metals decreases sharply. The phosphine ligand resin polymers of phosphine oxyphosphate and quaternary phosphine salts in Comparative Examples 4 and 5 exhibited poor desorption capacity for noble metals, indicating that the valence state and structure of the phosphine ligands significantly influence the desorption capacity. In Comparative Examples 5 and 6, due to the large steric hindrance surrounding S and N, they did not promote the desorption of noble metals but rather had the opposite effect, performing worse than the scheme using only phosphine ligands (Example 7).

[0078] Example 10

[0079] A mixed methanol solution containing Rh(III), Pd(III), Ir(III), Pt(III) and Na(I), Cu(II) metal ions at concentrations of 0.1 mol / L was prepared for later use. 10 g of the resin synthesized in Example 1 was placed in a fixed-bed continuous reaction tube (1 cm inner diameter), heated to 150 °C, and the above methanol solution was continuously fed in using a feed pump at a flow rate of 0.05 m / h. The effluent was collected, and the adsorption effect was tested using ICP. The results are listed in Table 2.

[0080] Table 2. Ion concentrations in the mixed solution after adsorption of resin material in Example 1

[0081]

[0082] As can be seen from Table 2, when the solution is replaced with an organic solution and a fixed-bed adsorption mode is adopted, the resin in Example 1 still shows good adsorption performance for noble metals Rh(III), Pd(III), Ir(III), and Pt(III), and can desorb to below 5 ppb, while exhibiting good selectivity.

[0083] Example 11

[0084] A 0.1 mol / L Pd(III) metal ion methanol solution was prepared. 100 ml of this solution was mixed with 10 g of the resin material prepared in Example 1. The adsorption temperature was controlled at -50 to 60 °C, and the adsorption time was 2 hours for each temperature range. The concentration of metal ions in the mixed solution was detected by ICP-MS after adsorption, and the results are shown in Table 3. The adsorption time was then increased to 24 hours, and the concentration of metal ions in the mixed solution was detected by ICP-MS after adsorption, and the results are shown in Table 4.

[0085] Table 3. Ion concentrations in the mixed solution after adsorption of resin material in Example 1

[0086]

[0087] Table 4. Ion concentrations in the mixed solution after adsorption of resin material in Example 1

[0088]

[0089] As can be seen from Table 3, when the adsorption time is 2 hours, the temperature has a relatively large impact on the adsorption effect. The higher the temperature, the more favorable it is for Pd adsorption. At -50℃, the Pd concentration after adsorption is 13 ppb, and at 60℃, the residual adsorption concentration is 2 ppb.

[0090] As shown in Table 4, extending the adsorption time to 24 hours still maintains a Pd residue level below 3 ppb after adsorption. Combining the data from Tables 3 and 4, although adsorption is slower at lower temperatures, extending the adsorption time still achieves good adsorption results. This should be adjusted based on actual production conditions.

[0091] Example 12

[0092] A 0.1 mol / L aqueous solution of Rh(III) metal ions was prepared. 100 ml of this solution was taken, and the pH was adjusted to 0-14 by adding 36% HCl and NaOH flakes. 10 g of the resin material prepared in Example 1 was added, and the adsorption temperature was controlled at 25°C for 2 hours. The concentration of metal ions in the mixed solution was detected by ICP-MS after adsorption, and the results are listed in Table 5.

[0093] Table 5. Ion concentrations in the mixed solution after adsorption of resin material in Example 1

[0094]

[0095] As can be seen from Table 5, when the pH is too low (0) or too high (greater than 8), the residual amount of Rh metal after adsorption increases significantly. This may be because the reaction is too acidic or too alkaline, affecting the interaction between Rh and the adsorption sites in the resin. When the pH is in the range of 1-10, the concentration of metal ions after adsorption can be maintained at a low level. This indicates that the resin beads are suitable for a wide pH range. Within the preferred pH range of 1-6, the resin beads have the best adsorption performance.

Claims

1. The application of a resin material as an adsorbent for noble metals in liquids, characterized in that... : The resin material is cross-linked into a resin material by means of one or more of the olefin-containing P-ligands (phosphine ligands) as polymerizing monomers, through olefin-based self-polymerization or copolymerization of one or more of the olefin-containing P-ligands with one or more of the olefin-containing S and / or N-ligands.

2. The application according to claim 1, characterized in that: The specific surface area of ​​resin materials is 20-2000 m². 2 / g, preferably in the range of 100-1200m 2 / g; pore volume is 0.1-5.0cm³ 3 / g, preferably 0.5-2.0cm 3 / g; pore size distribution is 0.01-100.0nm, preferably 0.1-20.0nm; In the copolymerization process, the molar ratio of the olefin-containing S and / or N second component to the phosphine ligand is 0.0001:1 to 10000:1 (preferably 0.001:1 to 1000:1).

3. The application according to claim 1, characterized in that: The resin material is prepared by self-polymerization of one or more P ligands containing olefin groups, or by self-polymerization or copolymerization of one or more P ligands containing olefin groups with one or more S and / or N ligands containing olefin groups. The P-ligand containing an olefin group comprises one or more monodentate or polydentate phosphine ligands, wherein the olefin group is preferably vinyl; it is selected from one or more of the following structures: Among them, L1-L59 are monophosphine ligands, and B1-B18 are multidentate phosphine ligands; The olefinic group in the S- and / or N-containing ligands containing an olefinic group is preferably vinyl, and the ligands containing an olefinic group S and / or N are selected from one or more of the following structures:

4. An application according to any one of claims 1-3, characterized in that: The preparation process of the resin material is as follows: After dissolving one or more phosphine ligands containing olefin groups, or, if a copolymerization scheme is adopted, adding one or more monomers containing olefin groups and S and / or N ligands, the olefin groups are polymerized by bulk polymerization, emulsion polymerization or suspension polymerization, and a free radical initiator is used to initiate the polymerization reaction of the olefin groups to generate a polymer. This polymer can be used as an excellent resin material for selectively adsorbing noble metals in liquids.

5. The application according to claim 4, characterized in that: The specific preparation steps of the resin material are as follows: a) Under an inert atmosphere of 273-473 K, add one or more phosphine ligands containing olefin groups to the solvent, or, when adopting a copolymerization scheme, add a second ligand containing olefin groups containing S and / or N, add a free radical initiator, and stir the mixture for 0.1-50 hours to obtain a prepolymer solution, with the preferred stirring time range being 1-10 hours; b) The prepolymer mixture obtained in step a) is subjected to polymerization reaction (by bulk polymerization, suspension polymerization or emulsion polymerization) under an inert atmosphere of 273-473K for 1-100 hours to obtain a phosphine-containing organic polymer. c) Remove the solvent from the phosphine-containing organic polymer obtained in step b) to obtain an organic polymer with a hierarchical porous structure containing exposed P, or P with S and / or N, which is the resin material that selectively adsorbs noble metals.

6. The application according to claim 5, characterized in that: The organic solvent in step a) is one or more of the following: benzene, toluene, xylene, biphenyl, polychlorinated biphenyl, cyclohexane, n-octane, dodecane, methanol, ethanol, dichloromethane, chloroform, 1,4-dioxane, tetrahydrofuran, and methyltetrahydrofuran. The free radical initiator mentioned in step a) is one or more of cyclohexanone peroxide, benzoyl peroxide, tert-butyl hydroperoxide, or azobisisobutyronitrile; In step b), when suspension polymerization or emulsion polymerization is adopted, the suspension emulsifier is selected from one or more of polyvinyl alcohol, polyvinylpyrrolidone, p-octylphenol polyoxyethylene ether, N-dodecyl dimethylamine, sodium stearate and calcium dodecylbenzenesulfonate; the volume ratio of oil phase to water phase in suspension or emulsion polymerization is 10000:1-1:10000 (preferably 1000:1-1:1000); In step a), before polymerization into an organic polymer, the concentration of the phosphine ligand containing an olefin group in the solvent ranges from 0.01 to 1000 g / L, preferably from 0.1 to 100 g / L, the molar ratio of the second component containing an olefin group (S and / or N) to the phosphine ligand is 0.0001:1 to 10000:1 (preferably 0.001:1 to 1000:1), and the molar ratio of the phosphine ligand containing an olefin group to the free radical initiator is 5000:1 to 10:1, preferably 1000:1 to 10:

1. The inert gas mentioned in steps a) and b) is selected from one or more of Ar, He, N2 and CO2.

7. The application according to any one of claims 1-3, characterized in that: The liquid is one or more of the following: industrial wastewater containing precious metals, electronic waste containing precious metals, and ore leachate containing precious metals, with the resin material used as an adsorbent for the recovery of precious metals; or, the liquid is a solution from a pharmaceutical production or preparation process or a solution from a food production or preparation process, with the resin material used as an adsorbent for the ultrapurification of pharmaceuticals or food, etc.

8. The application according to claim 7, characterized in that: The adsorption operation of resin materials as adsorbents can be carried out in fixed bed, moving bed or fluidized bed adsorption modes.

9. The application according to any one of claims 1-3 or 7 or 8, characterized in that: Because it is formed by olefin crosslinking, the resin material has stable physicochemical properties under the condition of adsorbing noble metals, is resistant to acids and alkalis, and can be used for the selective separation of noble metals in complex organic and / or inorganic solutions, preferably inorganic solutions. The operating temperature range is -50-400℃ (preferably -50-60℃), and the pH range is 1-13, preferably 1-6. Because of the high concentration of adsorption sites P, or P, S and / or N in the resin material skeleton, the adsorption loading of precious metals is large and the selectivity is high. It can efficiently and selectively adsorb and separate one or more of the noble metals such as Pt, Pd, Rh, and Ir in complex organic and / or inorganic solutions, without being affected by other metals, and can ultimately control the residual amount of noble metals in the solution after adsorption to below 10 ppb.

Citation Information

Patent Citations

  • A P-containing organic polymer, its preparation method and application

    CN105777988B

  • A method for separating platinum and rhodium from alkaline cyanide solution using polystyrene-tributyl quaternary phosphine resin

    CN109385525B

  • Resin for separating and gathering the valuable metal

    CN86103557A